2021
DOI: 10.1177/17483026211065387
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Milk-run route for inbound logistics of auto parts under low-carbon economy

Abstract: Greenhouse gas emissions have brought serious negative impacts on human beings and organisms, so energy saving and emission reduction have been recognized by more and more people. Traditional Milk-run model seldom considers the factors of energy saving and emission reduction, and its routing optimization cannot meet the current needs of low-carbon economic development. On the basis of traditional Vehicle Routing Problem research, considering the fixed cost, time penalty cost, energy consumption cost and carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In addition, the average energy consumption per weight unit was 0.089 kW/kg in the case of conventional supply optimization and 0.053 kW/kg in the case of real-time routing. This reflects a 40.4% energy saving, which concurs with the previous study [6] that showed how the optimization model helped to minimize travel distance and with other studies [13,17,24] where using I4.0 optimization and milk-run routes raised the energy efficiency for manufacturing systems in the automotive industry. Further, this supports the previous studies [22,25] that showed a positive impact of I4.0 technologies on the scheduling processes in manufacturing systems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the average energy consumption per weight unit was 0.089 kW/kg in the case of conventional supply optimization and 0.053 kW/kg in the case of real-time routing. This reflects a 40.4% energy saving, which concurs with the previous study [6] that showed how the optimization model helped to minimize travel distance and with other studies [13,17,24] where using I4.0 optimization and milk-run routes raised the energy efficiency for manufacturing systems in the automotive industry. Further, this supports the previous studies [22,25] that showed a positive impact of I4.0 technologies on the scheduling processes in manufacturing systems.…”
Section: Discussionsupporting
confidence: 90%
“…In another study in Turkey [6], an optimization model was presented to minimize the transportation cost by minimizing the travel distance and maximizing vehicle capacity while it tackled a milk-run situation. It was also considered [24] as a solution to minimize carbon emissions and reduce the distribution cost of logistics enterprises, and it was described as a win-win situation for social and economic aspects. In another consideration for forward and reverse milk-run vehicle routing and scheduling, constraints imposed by an in-plant distribution network were modeled [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of milkrun supply solutions is especially important in the case of high-frequency, small quantity demands, therefore the supply of manufacturing and assembly plants is a potential application field of milkrun supply solutions. The design aspects can include the cost reduction, the improvement of energy efficiency and the emission reduction [5].…”
Section: Introductionmentioning
confidence: 99%